Quantitative estimates of glacial refugia for chimpanzees (Pan troglodytes) since the Last Interglacial (120, 000 BP). Issue 10 (16th August 2021) - Barratt, Christopher D.; Lester, Jack D.; Gratton, Paolo; Onstein, Renske E.; Kalan, Ammie K.; McCarthy, Maureen S.; Bocksberger, Gaëlle; White, Lauren C.; Vigilant, Linda; Dieguez, Paula; Abdulai, Barrie; Aebischer, Thierry; et al.
Abstract: Paleoclimate reconstructions have enhanced our understanding of how past climates have shaped present‐day biodiversity. We hypothesize that the geographic extent of Pleistocene forest refugia and suitable habitat fluctuated significantly in time during the late Quaternary for chimpanzees ( Pan troglodytes ). Using bioclimatic variables representing monthly temperature and precipitation estimates, past human population density data, and an extensive database of georeferenced presence points, we built a model of changing habitat suitability for chimpanzees at fine spatio‐temporal scales dating back to the Last Interglacial (120, 000 BP). Our models cover a spatial resolution of 0.0467° (approximately 5.19 km 2 grid cells) and a temporal resolution of between 1000 and 4000 years. Using our model, we mapped habitat stability over time using three approaches, comparing our modeled stability estimates to existing knowledge of Afrotropical refugia, as well as contemporary patterns of major keystone tropical food resources used by chimpanzees, figs (Moraceae), and palms (Arecacae). Results show habitat stability congruent with known glacial refugia across Africa, suggesting their extents may have been underestimated for chimpanzees, with potentially up to approximately 60, 000 km 2 of previously unrecognized glacial refugia. The refugia we highlight coincide with higher species richness for figs and palms. Our results provide spatio‐temporally explicit insights into the role of refugia across the chimpanzee range, forming the empirical foundation for developing and testing hypotheses about behavioral, ecological, and genetic diversity with additional data. This methodology can be applied to other species and geographic areas when sufficient data are available. Abstract : Quantitative estimates of glacial refugia years for chimpanzees over the past 120, 000 using climate and human density data. Highlights: Chimpanzee habitat suitability mapped to 120, 000 kya at high spatio‐temporal resolution. Stability congruent with known refugia but reveals additional areas. Foundation for future comparative analyses of behavioral/genetic diversity patterns.